Association of Complementary Feeding Practices and Nutritional Status Among Infants Aged 9–12 Months: Hubungan Praktik Pemberian MP-ASI dan Status Gizi Bayi 9–12 Bulan - Lia Nurul Izza; Noor Hidayah; Umi Faridah (Academia Open, 2026)
ABSTRACTGeneral Background: Complementary feeding during the first two years of life is fundamental to achieving optimal infant nutritional status. Specific Background: Undernutrition remains present among infants in the working area of Puskesmas Sarang 2 despite high exclusive breastfeeding coverage and timely MP-ASI initiation. Knowledge Gap: Local evidence assessing the association between complementary feeding quality—food type, portion adequacy, and feeding schedule—and nutritional status in infants aged 9–12 months is limited. Aims: This study examined the relationship between complementary feeding practices and nutritional status among infants aged 9–12 months. Results: Using a cross-sectional analytic design with total sampling of 89 infants, 87.6% received appropriate MP-ASI and 78.7% had good nutritional status. Spearman’s rho indicated a strong positive and significant correlation (r = 0.753; p < 0.001), with appropriate practices predominantly linked to good nutritional status, while inappropriate practices were mainly associated with undernutrition. Novelty: This study integrates timing, type, portion, and schedule of MP-ASI within a single local analytical framework. Implications: Targeted nutrition counseling and routine monitoring at primary healthcare and posyandu levels are essential to prevent undernutrition and support optimal growth. Highlights:• A strong positive correlation was identified between feeding patterns and anthropometric classification (r = 0.753; p < 0.001).• Most respondents demonstrated appropriate menu variation, portion adequacy, and meal scheduling.• Undernourished cases were concentrated among infants with inappropriate dietary practices. Keywords: Complementary Feeding Practices; Nutritional Status; Infants Aged 9–12 Months; Cross-Sectional Study; Primary Healthcare